الآثار المحتملة لإقامة منطقة تجارة حرة بين مصر و روسيا على تدفقات التجارة البينية : دراسة تطبيقية باستخدام نموذج الجاذبية - عارف، فؤاد محمد عيسى (جامعة عين شمس - كلية التجارة, 2012)
In view of the recent wave of worldwide sub regional and bilateral trade cooperation, and the recent suspension of Doha negotiations by the world Trade Organization, the opportunity costs of not moving toward greater trade integration among some certain countries could be increasing. \ \ This paper presents the recent trends in the Egypt-Russia trade and examines empirically the likely impact of their free trade agreement on bilateral trade flows, i.e. trade creation and diversion effects, using gravity model under different comparative static scenarios. \ \ The results of the analysis revealed several interesting observations. Our analysis of the total trade indicates that FTA brings about trade creation effect and that trade diversion effect is limited.
Keywords: التجارة البينية -- التجارة الخارجية -- التبادل التجاري -- الاتفاقيات التجارية -- روسيا -- مصر -- الأسواق الحرة -- التكامل الاقتصادي -- التعاون الاقتصادي -- الاتفاقيات التجارية -- الميزان التجاري -- الناتج المحلي الإجمالي -- الصادرات -- أسعار الصرف -- أسعار الفائدة -- التكتلات الاقتصادية -- الرسوم الجمركية -- حقوق الملكية الفكرية -- الاستثمارات الأجنبية